A thermography-based method for fatigue behavior evaluation of coupling beam damper - Zhe Zhang; Jinping Ou; Dongsheng Li; Shuaifang Zhang; Junling Fan (Fracture and Structural Integrity)
Under cyclic load, local fatigue damage will occur in the metal damper widely used in the shear wall. This will deteriorate the stiffness of damper and weaken the hysteresis behaviour. The present paper proposed a new and easy method to manufacture kinds of coupling beam dampers. A thermography-based experiment was used to study the energy dissipation and damage accumulation during fatigue process of the metal damper. Based on the temperature variation related to fatigue damage process, the relationship between the plastic deformation and thermal energy dissipation was quantitatively established. Besides, the relationships between the temperature increase to damage accumulation and mechanical load were analyzed systematically.